EXAMINATION OF OCCUPATIONAL RESILIENCE BELIEFS OF INSERVICE AND PRE-SERVICE EARLY CHILDHOOD EDUCATION TEACHERS ACCORDING TO DIFFERENT VARIABLES - (:unkn) unknown (My University, 2018)
Occupational resilience contributes teachers to adapt difficult conditions of teaching, to deal with obstacles and to maintain professional commitment. The purpose of this research is to compare the occupational resilience beliefs of early childhood education teachers and preservice teachers. In accordance with this purpose, whether there is a significant difference between the occupational resilience beliefs of teachers and pre-service teachers, whether there is a significant difference in the occupational resilience beliefs of teachers according to their seniority and whether there is a significant difference in the occupational resilience beliefs of pre-service teachers according to type of university, the relational screening model has been used. The data is collected from 275 participants via Occupational Resilience Beliefs Scale for Teacher Candidates. As the results of statistical analysis, there is a significant difference in the occupational resilience beliefs of early childhood education teachers and pre-service early childhood education teachers in favor of early childhood education teachers. On the other hand, there is no significant difference in the ccupationalresilience beliefs of teachers according to their seniority. There is no significant difference in the occupational resilience beliefs of pre-service teachers according to the type of university. The findings are discussed in the framework of the relevant literature.